The Role of the Independent Student Exchange Program in Increasing Student Tolerance Attitude - Apriliyanto, Erwin; Sulfiani, Besse; Lasmi, Hardiyanti; Jungso, Amir; Hasanah, Niswayanti; Jumrah, Jumrah (Journal of Universal Community Empowerment Provision, 2024)
This research aims to find out the role of the Independent Student Exchange Program in increasing student tolerance. This study used qualitative research methods. This research uses various written data sources such as articles, documents and government policies related to education. The results of this research show that the Nusantara Module activities with four activity points consisting of, diversity, reflection, inspiration and social contribution provide a very big impact and role in increasing the tolerance attitude of Independent Student Exchange Program students as well as providing opportunities for Exchange Program students. Merdeka Students' ability to carry out the learning process together with regular students of the recipient universities further strengthens the tolerant attitude of the students of the Merdeka Student Exchange Program system.